2022
DOI: 10.1037/rep0000448
|View full text |Cite
|
Sign up to set email alerts
|

Relations among gratitude, adaptation to disability, and flourishing among adults with disabilities: A longitudinal mediation model.

Abstract: Purpose/Objective: Flourishing, a primary outcome of rehabilitation psychology, is understudied among adults with disabilities. Gratitude has emerged as an individual strength that is both malleable and robust in predicting flourishing and adaptation to disability. The purpose of this study was to assess the influence of gratitude on flourishing over time and to analyze the potential mediating role of adaptation to disability on this relationship for a group of adults with disabilities. Research Method/Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Research conducted by Tessy et al (2022), which examined the correlation between gratitude and forgiveness on flourishing, also strengthens the results of this study that gratitude affects the flourishing rate and has a greater contribution to increasing flourishing than other criterion variables, namely forgiveness. Another study that corroborated the results revealed that gratitude influenced flourishing by 27% with adjustments to disability as a moderator variable (Phillips et al, (2022).…”
Section: Variablementioning
confidence: 56%
“…Research conducted by Tessy et al (2022), which examined the correlation between gratitude and forgiveness on flourishing, also strengthens the results of this study that gratitude affects the flourishing rate and has a greater contribution to increasing flourishing than other criterion variables, namely forgiveness. Another study that corroborated the results revealed that gratitude influenced flourishing by 27% with adjustments to disability as a moderator variable (Phillips et al, (2022).…”
Section: Variablementioning
confidence: 56%
“…Gratitude at the trait level, which describes the steady tendency to respond to certain types of emotional responses, is defined as the predisposition to be aware of when the self is a benefactor of some positive outcome or good deed, often attributed to the actions of other people (McCullough et al, 2002). Multiple studies demonstrate that gratitude could function as a protective factor by facilitating the development of social relationships, and that people who have higher levels of gratitude tend to exhibit fewer negative perceptions of themselves and others (Lee, 2022;Phillips et al, 2022;Smith et al, 2016;Wood et al, 2010;. Studies among student veterans also suggest that gratitude may buffer their psychological health risks by demonstrating negative associations with perceived stress and suicidal ideation Valikhani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Emphasizing positive psychological traits to promote happiness in individuals with disabilities can further benefit rehabilitation research, clinical practice, and consumer experiences (Chou et al, 2013; Dunn & Dougherty, 2005). Therefore, rehabilitation researchers and practitioners have been advocating for a paradigm shift from examining deficits in disability to focusing on positive psychosocial factors, including happiness (Chou et al, 2013; Dunn & Dougherty, 2005; Dunn et al, 2009; Fortuna et al, 2020; Huck et al, 2022; Grenawalt et al, 2022; Lee, 2022; Lee, Rumrill, et al, 2022; Lee, Rumril, Tansey, 2022; Moser et al, 2020; Phillips et al, 2022; Sánchez et al, 2019; Umucu, Lee, Berwick, et al, 2022; Umucu, Reyes, Carrola, et al, 2021; Umucu, Tansey, et al, 2021; Umucu, Wu, et al, 2020).…”
mentioning
confidence: 99%